Comparison between Pakistani Kashi Tiles and Persian Kashan Tiles - Qurat ul Ain (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2019)
Kashi tiles are the traditional ceramic tiles of Pakistan. They have been produced in Pakistan (previously India) for centuries now; they were brought to India by Persian potters of city Kashan. This paper is in effort to remedy the regrettable absence of documentation of Kashi tiles in the heritage of Muslim enamel tiles. The purpose was to investigate the connection between Persian and Kashi tiles and analyze their similarities and differences. The hypothesis is investigated by literature review of different books and research papers and by interviewing Kashikar of Pakistan about their practices and they were studied and compared. The results and conclusions of this study are the ceramists have very limited knowledge and have refused to accept any new idea due to their loyalty to the craft. They believed in keeping the original recipe intact and have firmly refused to experiment and explore. These tiles were never exactly same to Seljuk blue and white tiles; and the forefathers of these ceramists had obviously studied their environment and experimented with local raw materials. However it is clear from the close remembrance in Design and color palate of these crafts that the original migrated potters were definitely recreating the blue and white craft of Persia, that was imitation of Chinese porcelain